Oyster hemocytes express a proline-rich peptide displaying synergistic antimicrobial activity with a defensin - Gueguen, Yannick; Romestand, Bernard; Fievet, Julie; Schmitt, Paulina; Destoumieux Garzon, Delphine; Franck, Vandenbulcke; Philippe, Bulet; Bachere, Evelyne (Molecular Immunology, 2009)
A cDNA sequence that encodes a 61-amino acid polypeptide precursor with homologies to proline-rich antimicrobial peptides (AMPs) was identified in the oyster Crassostrea gigas. After release of a hydrophobic signal peptide. the resulting 37-amino acid peptide, Cg-Prp, is composed of an acidic region and a cationic proline-rich region. To evaluate the biological properties of Cg-Prp, multiple proline-rich peptides corresponding to putative processing of the full-length Cg-Prp were synthesized. A limited antimicrobial activity was observed for two of them, which also showed strong synergistic antimicrobial activity with Cg-Def, a defensin from C gigas. To our knowledge, this is the first evidence of synergy between a defensin and another AMP in an invertebrate. By in situ hybridization, the expression of Cg-prp was found to be restricted to hemocytes and induced following bacterial challenge. Cg-prp transcripts were also detected in hemocytes infiltrating mantle, where Cg-Def is expressed. Additionally, by immunocytochemistry, we showed that Cg-Prp or one of its variants is present in some hemocytes together with defensins. In conclusion, we described here the first proline-rich AMP from mollusk. From our study, it is likely to provide a first line of defense against bacterial invasion by acting through synergy with defensins. (C) 2008 Elsevier Ltd. All rights reserved.